Dynamic behavior of positron acoustic multiple-solitons in an electron-positron-ion plasma - Salam, Md. Abdus; Akbar, M. Ali; Ali, M. Zulfikar; İnç, Mustafa (Springer, 2024)
We explore the dynamic characteristics of positron acoustic multiple-solitons in an unmagnetized plasma containing mobile cold positrons, Kappa-distributed superthermal hot electrons and positrons, and stationary positive ions. This study investigates the overtaking collisional effects, various parametric impacts, and phase shifts in the electron-positron-ion (e-p-i) plasma. Through the reductive perturbation technique, we derived the Korteweg-de Vries (KdV) equation and the modified Korteweg-de Vries (mKdV) equation. The multiple-soliton solutions (MSS) are then obtained using the simplified Hirota method and Cole-Holf transformation. The investigation shows that the amplitudes and widths of multi-solitons decrease with the increasing hot positron concentration but increase with the increasing hot electron index parameter. The results are expected to help us understand the dynamics of waves propagation in the pulsar magnetosphere, the active galactic nuclei, the quasar's relativistic jet, the inner region of the accretion disk surrounding a black hole, etc.
Keywords: Positron-acoustic waves; Simplified Hirota method; Phase shift; KdV equation; mKdV equation